Islamic banks: Contrasting the drivers of customer satisfaction on image, trust, and loyalty of Muslim and non-Muslim customers in Malaysia - Amin, Muslim; Zaidi, Isa; Fontaine, Rodrigue Ancelot Harvey (Emerald Group Publishing Limited, 2013)
The purpose of this study is to investigate customer satisfaction and its effect on image, trust, and customer loyalty for Islamic banks. The study uses data from Islamic banks and dual-window Islamic banks, pertaining to two different customer segments (Muslims and non-Muslims). Findings – The results indicate that customer satisfaction has a significant relationship with image, image has a significant relationship with trust, and trust has a significant relationship with customer loyalty for both customer segments. Furthermore, significant differences occur in the effect of customer satisfaction on image, image on trust, and trust on customer loyalty between Muslim and non-Muslim customers.